RESISTENSI WAYANG SADAT DALAM MENGHADAPI HEGEMONI MUHAMMADIYAH - Muhammad Mukti (Jurnal Penelitian Humaniora, 2008)
The Muhammadiyah Organization in Trucuk-Klaten in the recent period is truly a puritan movement which commits in eradicating the polytheist (musyrik), tahayul, bid’ah, churofat (TBC). The lived-Sadat puppet is flourishing in Tucuk as the part of the art tradition which considers by Muhammadiyah as full of polytheist TBC. Therefore, it becomes the target of eradicating (to hegemony). However, the Sadat puppet is also re-against by defending its existence in many ways. This research is aimed to reveal the form of hegemony of Muhammadiyah Trucuk to the Sadat puppet, and the resistance of Sadat puppet toward that hegemony. The research shows that there are 2 forms of Muhamamdiyah Trucuk’s hegemony to the Sadat puppet. The first is internal hegemony, and the second is external hegemony. Meanwhile, the forms of resistance of Sadat puppet toward the hegemony of Muhammadiyah are the opened resistance and the closed resistance.